PRESERVICE ENGLISH TEACHERS’ VIEWS ON ONLINE LANGUAGE ASSESSMENT IN TURKEY - Yeşilçınar, Sabahattin (My University, 2024)
Technology has rapidly accelerated the adoption of online language assessments (OLA), presenting unique opportunities and challenges. This study explores preservice English teachers’ views on OLA in Turkish Turkey. Using a qualitative phenomenological approach, interviews were conducted with 11 English preservice teachers from a state university in Turkey. The findings reveal both the advantages and disadvantages of OLA. On the positive side, preservice teachers highlighted the environmental and financial benefits of reducing paper use and operational efficiencies like automated grading and the flexibility of remote assessments. They also appreciated the enhanced learning experiences provided by multimedia and interactive elements and the innovative assessment opportunities offered by online platforms. However, significant challenges were identified, including technical and infrastructure barriers, varying levels of digital literacy, and concerns about assessment integrity and security. Psychological challenges were also prominent, with many preservice teachers experiencing increased stress and anxiety due to unfamiliarity with online formats and the pressures of adapting to new technologies. These insights underscore the need for comprehensive training and support to help preservice teachers navigate the complexities of OLA, ensuring both effective implementation and the well-being of future educators.
Keywords: Preservice teachers; educational technology; Online language assessment